2019
DOI: 10.3390/polym11071129
|View full text |Cite
|
Sign up to set email alerts
|

Flame Retardancy and Toughness of Poly(Lactic Acid)/GNR/SiAHP Composites

Abstract: A novel flame-retardant and toughened bio-based poly(lactic acid) (PLA)/glycidyl methacrylate-grafted natural rubber (GNR) composite was fabricated by sequentially dynamical vulcanizing and reactive melt-blending. The surface modification of aluminum hypophosphite (AHP) enhanced the interfacial compatibility between the modified aluminum hypophosphite by silane (SiAHP) and PLA/GNR matrix and the charring ability of the PLA/GNR/SiAHP composites to a certain extent, and the toughness and flame retardancy of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…In another investigation [ 301 ], a novel flame retardant and toughened bio-based (PLA)/glycidyl methacrylate-grafted natural rubber (GNR) composite was reported. The interfacial compatibility between PLA/GNR matrix and the charring ability of the PLA/GNR/SiAHP composites as well as the modified aluminum hypophosphite by silane (SiAHP) was enhanced to a certain extent due to the surface modification of AHP.…”
Section: Trends Of Pla and Phas Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In another investigation [ 301 ], a novel flame retardant and toughened bio-based (PLA)/glycidyl methacrylate-grafted natural rubber (GNR) composite was reported. The interfacial compatibility between PLA/GNR matrix and the charring ability of the PLA/GNR/SiAHP composites as well as the modified aluminum hypophosphite by silane (SiAHP) was enhanced to a certain extent due to the surface modification of AHP.…”
Section: Trends Of Pla and Phas Applicationsmentioning
confidence: 99%
“…The promising flame retardancy of the PLA/GNR/SiAHP composites was suggested to be due to the synergistic effect including condensed and gaseous phase flame-retardant mechanisms. High-performance flame-retardant PLA/GNR/SiAHP composites have great potential applications as alternatives to petroleum-based polymers in the building and automotive interior sectors [ 301 ].…”
Section: Trends Of Pla and Phas Applicationsmentioning
confidence: 99%
“…In addition, as a small molecule relative to PLA, PAPh occupied the space between the PLA chain, thereby reducing the energy required for molecular movement. [ 43 ] The multiple phenyl groups in PAPh promoted the accumulation of PLA segment at low temperatures to form an ordered crystalline structure. [ 44 ] However, with the increase of PAPh, partial aggregation was observed between PAPh and decreased the crystallinity of PLA.…”
Section: Resultsmentioning
confidence: 99%
“…Attempts have been made to simultaneously improve the toughness and flame retardancy of PLA by using a combination of a toughening agent such as poly (ethylene glycol) (PEG) and a flame retardant, taking APP for an example. [20][21][22][23] It has also been reported that a multifunctional additive was applied to concurrently improve the toughness and flame retardancy of PLA. For example, Zhang et al synthesized a multifunctional biobased flame retardant/graphene oxide hybrid (GOH) for PLA, the addition of 10 wt% of GOH enables PLA to achieve a desirable UL-94 V-0 rating, however, the elongation at break increased by only five times.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, high‐performance PLA composites with an integrated toughness and flame retardancy is highly desirable. Attempts have been made to simultaneously improve the toughness and flame retardancy of PLA by using a combination of a toughening agent such as poly (ethylene glycol) (PEG) and a flame retardant, taking APP for an example 20–23 . It has also been reported that a multifunctional additive was applied to concurrently improve the toughness and flame retardancy of PLA.…”
Section: Introductionmentioning
confidence: 99%